Pola penerapan social emotional learning dalam pembelajaran matematika di sekolah dasar - Putri, Vihayuning; Mahfud, Hasan; Surya, Anesa (Universitas Sebelas Maret, 2024)
This research aims to describe the pattern of implementing Social Emotional Learning (SEL) in mathematics learning for fifth grade students at SD Djama'atul Ichwan Surakarta. This research uses a qualitative approach with a case study method. The subjects of this research were class teachers and 28 students. This research uses observation, interviews, questionnaires and document study techniques. Testing the validity of the data uses triangulation of time and techniques. The data analysis model uses the Creswell model. Results showed teachers utilized supportive classroom environment approaches, integration of SEL and Academic Instruction, and explicit SEL Instruction. The teacher carries out several activities that have become routine, thus forming a clear pattern. The approach used can shape students' SEL competencies, including self-awareness, self-management, social awareness, relationship skills, and responsible decision making. The use of the SEL approach in mathematics learning indirectly influences mathematics learning outcomes. Therefore, it is important for teachers to integrate SEL into mathematics learning. The implication of this research is that it can increase scientific insight regarding the application of SEL to both teachers and students. The recommendation from researchers is that SEL can be further optimized in its implementation in a massive and structured manner.Kata kunci: social emotional learning, approach, competencies, mathematics, academic achievement, and elementary school